The Legal Strength of the King's Recommendation as a Condition for the Candidacy of the Head of Ohoi and/or Finua in Tual City - Reniuryaan, Abd Kadir; Pietersz, Jemmy Jefry; Matitaputty, Merlien Irene (PAMALI: Pattimura Magister Law Review, 2026)
Introduction: Tual City is one of the cities in Maluku Province that still applies local wisdom in daily life, one of which is in terms of the election of the Village Head. The basis for the implementation of the village head election by applying local wisdom is based on the establishment of several Regional Regulations that change the status of the village to a customary village called Ohoi and/or Finus, this certainly has an impact on the requirements for the nomination of village heads, one of which is to get the King's Recommendation.Purposes of the Research: The purpose of this article is to examine and analyze the legal force of the king's recommendation as a requirement for nominationas head of ohoi and/or finua in Tual City.Methods of the Research: This research is normative juridical research. This type of research is descriptive analysis. Supporting data and information are then identified and then systematized for interpretation and arguments are given to reach conclusions about the problem.Results Main Findings of the Research: The results of this study indicate that the Legal Power of the King's Recommendation in the Nomination of Village Heads Recommendations given by the traditional king in the process of nominating village heads in Tual City have a strong legal standing, both from the perspective of customary law and positive law. In the Larvul Ngabal customary system, the traditional king is the highest leader who has the authority to give approval to village head candidates who are deemed to meet the criteria of customary values and social harmony. Formally, this recommendation is recognized by the local government through regional regulations and is strengthened by the provisions of Law Number 6 of 2014 concerning Villages. Dynamics and challenges of implementation Although legal recognition has existed, the practice of implementing the king's recommendations still faces various challenges, such as differences in interpretation of authority between traditional institutions and the formal government, potential conflicts of interest, and social changes that influence community perceptions of the role of customary law.